Physical characteristic of briquette charcoal derived from carbonization of food waste via microwave technique: article / Nabihah Azron and Dr. Siti Shawalliah Idris - Azron, Nabihah; Idris, Siti Shawalliah (2018)
Food waste disposal at the landfills is a crucial problem to government and people in Malaysia since the landfills is unable to support big amount of food waste anymore. An alternative solution is by transforming the food waste into beneficial product such as briquette charcoal using microwave pyrolysis technology. This research investigates the potential of solid char from food waste to become briquette charcoal with addition of binder. The main objective in this study is to investigate the effect of binder and blending ratio on briquetting ability of food waste charcoal in terms of the physical characteristic and energy content. Microwave pyrolysis method was used to convert food waste into fully pyrolysed solid char under parameter: 30 minutes of radiation time, 1000 W microwave power, 200 ml/min nitrogen flow and mass loading of 200g. Binders involve in this research are starch and carboxymethyl cellulose (CMC). A good quality of charcoal briquette has capability to withstand impact during packaging, handling and transportation. Standard physical characteristic that were tested for briquette includes moisture content, compressive strength and impact resistance. Calorific value of briquette was studied to analyze energy content in the briquette. Thus, briquette charcoal with 10% CMC (S3) is the most ideal to become a quality briquette due to its suitable calorific value (21.171 MJ/kg), moisture content (6.2312%), compressive strength (0.813 MPa) and impact resistance (99.81%). This finding is beneficial for briquette industry in the development of green product using biomass, but further research is essential before production of briquette take place.